Mapping Purchasing Item to Improve Procurement Process on Smelter Project at PT. X - Sinaga, Rovid Hot Budiman (Avenew Indonesia, 2025)
The procurement process in large-scale projects such as smelter construction is key in ensuring the overall success of the project, especially in the context of cost, time, and quality. The main problem that occurs at PT X is the occurrence of significant cost overruns caused by inefficiencies in the procurement process, such as errors in planning needs, delays in delivery, and mismatches in item specifications. This study aims to map purchasing items using the Kraljic Matrix based on supply risk and profit impact to develop a more strategic procurement approach. This research uses a quantitative approach with a survey method to procurement employees at PT X. As for mapping PT X's purchasing items, material classification will be carried out based on the Kraljic Matrix to identify strategic items. By classifying items into four categories—non-critical, leverage, bottleneck, and strategic—the company can apply differentiated procurement tactics for better risk and cost control.